Port choice in Brazil: A qualitative research related to in-depth interviews - Felipe Lobo Umbelino de Souza; Cira Souza Pitombo; Dong Yang (Journal of Shipping and Trade (JST), 2021)
The choice of port is one of the topics that most interest researchers. Port selection behaviour may vary depending on port user perspectives. Prior studies have attempted to determine user preferences for certain port choice factors, but there are only few studies in developing countries, such as Brazil, where there is a lack of studies on this topic. The objectives of this article are to analyse the port selection factors in Brazil for different port users, to discuss the implications for competitiveness among ports and to assist port service providers to formulate strategies. Identifying factors will help port service providers to develop strategies in the Brazilian market. The paper explores the case of the Southeast region port market in Brazil, based on data from the port sector and in-depth interviews with a representative selection of port users and specialists in the port sector. The results suggest that Brazilian Port Administrations need to adopt strategies aimed at increasing connections with the interior of Brazil, but they also need to adopt a highly market-based approach, communicating and synchronizing strategies with different public and private stakeholders.
Keywords: 650; Brazilian shipping market; Port choice; Port competition; Port policy